(untitled) (Revista Lusófona de Educação, 2026)
This article presents an analytical account of a pedagogical experience developed in the teaching of Calculus within an Engineering program, grounded in the use of comic strips as a didactic, expressive, and assessment-oriented language. The methodological proposal, structured around four stages (Didactization, Challenge, Drawing, and Diagnosis), sought to address the question of how to promote inclusion, student engagement, and learner autonomy without compromising conceptual rigor. The results revealed increased student involvement, strengthened authorship, and expanded ways of understanding mathematical concepts. Comic strips proved to be a mediating language capable of translating complex technical ideas into meaningful narratives, contributing to more humane pedagogical practices that are sensitive to cognitive diversity and aligned with the formative demands of Engineering education. It is concluded that the integration of art, language, and science broadens the repertoire of innovative methodologies in higher education, contributing to the fields of Engineering Education and Mathematics Education, and pointing to new avenues of research on formative assessment, student authorship, and the humanization of Mathematics teaching.